2014
DOI: 10.1111/sed.12118
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary evolution and environmental history of Lake Van (Turkey) over the past 600 000 years

Abstract: The lithostratigraphic framework of Lake Van, eastern Turkey, has been systematically analysed to document the sedimentary evolution and the environmental history of the lake during the past ca 600 000 years. The lithostratigraphy and chemostratigraphy of a 219 m long drill core from Lake Van serve to separate global climate oscillations from local factors caused by tectonic and volcanic activity. An age model was established based on the climatostratigraphic alignment of chemical and lithological signatures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
151
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(158 citation statements)
references
References 89 publications
6
151
0
1
Order By: Relevance
“…Sediment properties like porosity or permeability are highly variable at both Lake Van sites due to rapid changes from laminated sediments to chaotic, mass-wasting sediments of variable composition and tephra layers of variable thickness. All lithologies can be found at both sites (Stockhecke et al 2014), albeit in variable thickness and stratigraphic position. Still, at any given depth, cell abundance at both sites is very similar, independent of lithology in the respective sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment properties like porosity or permeability are highly variable at both Lake Van sites due to rapid changes from laminated sediments to chaotic, mass-wasting sediments of variable composition and tephra layers of variable thickness. All lithologies can be found at both sites (Stockhecke et al 2014), albeit in variable thickness and stratigraphic position. Still, at any given depth, cell abundance at both sites is very similar, independent of lithology in the respective sample.…”
Section: Discussionmentioning
confidence: 99%
“…In summer 2010, long sediment cores were retrieved from two sites, recording palaeoenvironmental changes of the last 600 ky in this climate-sensitive area (Litt et al 2009;Stockhecke et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The recent International Continental Drilling Project (ICDP) PALAEO-VAN project has focused on coring the varved sediments from two locations within Lake Van (Litt et al 2009(Litt et al , 2012Cukur et al 2014;Litt & Anselmetti 2014;Stockhecke et al 2014). Work is ongoing to establish the chronology, but Litt et al (2009) observe extensive seismites in the test drill cores, attributing them to the repeated occurrence of earthquakes throughout the last 500 ka.…”
Section: Geological Settingmentioning
confidence: 99%
“…By adding radiometric dating techniques, the Lake Van chronology was correlated by using "age control points", derived from visual synchronization with the GICC05-based NGRIP isotope data for this relevant interval (0-116 ka;NGRIP members, 2004;Rasmussen et al, 2006;Svensson et al, 2008;Wolff et al, 2010). Additionally, a correlation with three 40 Ar / 39 Ar dated onshore tephra layers was implemented in the age-depth model of the composite profile, i.e., the Nemrut Formation (NF) at 32.70 ± 2.55 ka BP, the Halepkalesi Pumice (HP-10) fallout at 61.60 ± 2.55 ka BP as well as the Incekaya-Dibekli Tephra at ∼ 80 ka BP (Stockhecke et al, 2014b;Sumita and Schmincke, 2013). Within the last glacial period, the paleomagnetic Laschamp excursion at ∼ 41 ka BP (Vigliotti et al, 2014) could be identified in the core sequence.…”
Section: Chronologymentioning
confidence: 99%
“…Here we want to stress that, among data sets used for visual correlation, pollen data published in show the glacial-interglacial changes with the largest signal amplitude. However, the age-depth model of Stockhecke et al (2014b) is based on tuning with the NGRIP event stratigraphy. The correlation points of the Lake Van sedimentary record have been mainly defined by abiotic proxies (i.e., TOC) caused by a higher time resolution of this data set in comparison to the pollen samples available during that time.…”
Section: Chronologymentioning
confidence: 99%